2020
DOI: 10.1002/joa3.12479
|View full text |Cite
|
Sign up to set email alerts
|

Association between routine biomarkers and atrial fibrillation in patients undergoing implantation of a dual‐chamber pacemaker

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…On the other hand, there are data on changes in various biomarkers, which were also associated with an increased risk of tachyarrhythmia in PPM patients. In a study of adult PPM patients on the occasion of CVS, it was found that increased values of red blood cell distribution width (RDW) and γ-glutamyl transferase (γGT) in the serum were associated with an increased risk of AF [26].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there are data on changes in various biomarkers, which were also associated with an increased risk of tachyarrhythmia in PPM patients. In a study of adult PPM patients on the occasion of CVS, it was found that increased values of red blood cell distribution width (RDW) and γ-glutamyl transferase (γGT) in the serum were associated with an increased risk of AF [26].…”
Section: Introductionmentioning
confidence: 99%